The Effectiveness of Beetroot and Apple Juice Combination on Physical Endurance and Hemoglobin Levels in Sprague Dawley Rats - Setiawan, Deni; Moerfiah, Moerfiah; Yulianita, Yulianita (Journal of Science Innovare, 2024)
The present study investigates the stimulant and hematological effects of combined beetroot (Beta vulgaris L.) and apple (Malus pumila Mill.) juice on the physical endurance and hemoglobin (Hb) levels of Sprague Dawley rats. Adequate Hb concentration plays a critical role in oxygen transport and energy metabolism during physical activity. Thus, natural stimulant sources rich in bioactive compounds were evaluated as potential alternatives to synthetic energy supplements. Twenty-five male rats were divided into five treatment groups (n = 5): three groups receiving different ratios of beetroot and apple juice (1:1, 2:1, and 1:2), a negative control (CMC-Na 0.5%), and a positive control (caffeine 20 mg/200 g body weight). Stimulant activity was assessed using a rotarod endurance test, while Hb levels were measured by the Sahli method using a hemometer. The results demonstrated that the combined beetroot and apple juice significantly enhanced both endurance duration and hemoglobin concentration compared to the negative control (p 0.05). The optimal stimulant and hematopoietic effects were observed in the 2:1 beetroot-to-apple ratio, corresponding to doses of 5.6 g and 0.63 g per 200 g body weight, respectively. This combination yielded prolonged rotarod retention time and elevated Hb levels up to 18.5 g/dL, exceeding baseline and control values. The observed enhancement is attributed to the synergistic effects of bioactive constituents such as iron, potassium, flavonoids, and vitamin C, which facilitate oxygen transport, neuromuscular coordination, and erythropoiesis. These findings indicate that beetroot–apple juice exerts a physiological stimulant effect while improving hematological parameters without the adverse effects commonly associated with synthetic caffeine-based stimulants. This study highlights the potential of functional plant-based beverages as safe natural ergogenic aids for improving endurance and blood health.